A Study on the Association of Purchase Behavior and Social Media of Gen Z in Indonesia - Putra, Akira Wahyu (APPS Publications, 2024)
Purposes: This research aims to explore the association between social media usage and purchase behavior among Generation Z in Indonesia. Specifically, it seeks to understand how social media content and influencers impact the purchasing decisions of this demographic, providing insights that can inform digital marketing strategies tailored to Gen Z. Methodology: The study employs a quantitative research approach, utilizing primary data collected through online surveys. Purposive sampling was used, targeting individuals from Generation Z with experience using e-commerce platforms and active social media accounts. Data analysis was conducted using Smart Partial Least Square (SmartPLS) and Structural Equation Modeling (SEM) to test the proposed hypotheses. Findings: The research findings support the hypotheses that social media content and influencers significantly influence the purchase behavior of Indonesian Gen Z. The study reveals that engaging and visually appealing social media content, along with influencer endorsements, plays a crucial role in shaping the purchasing decisions of this demographic. Novelty: This research contributes to the existing literature by providing a focused analysis of the Indonesian Gen Z population, a demographic that has not been extensively studied in this context. The study also offers practical insights for businesses and policymakers aiming to enhance digital marketing strategies and e-commerce platforms for this specific audience. Research Implications: The study suggests that businesses should prioritize creating compelling social media content and leveraging influencer marketing to effectively reach and engage Gen Z consumers in Indonesia. Additionally, it highlights the need for improved ICT infrastructure to support the growing e-commerce landscape in the country.